The Impact of Transformational Leadership on the Level of Marketing Creativity for Employees of Jordanian Commercial Banks - Mohailan, “Mohammed Haider” Sadeq; Othman, Mohammad Ali Yahiya (The Arab Journal of Administration, 2024)
The study aimed to demonstrate the impact of transformational leadership in its dimensions, (ideal influence, inspirational motivation, intellectual stimulation, individual considerations, and empowerment) on marketing creativity in Jordanian commercial banks in the northern region. The study concluded that there is an impact of transformational leadership on marketing creativity in Jordanian commercial banks/ the northern region. There is also an impact of the ideal influence dimension, the inspirational motivation dimension, intellectual stimulation, individual consideration and empowerment on marketing creativity in Jordanian commercial banks in the northern region. The study followed the descriptive analytical approach, and a survey list was used as a tool to collect data from the study population consisting of marketing employees in Jordanian commercial banks in the northern region. The study concluded that, the banks studied possess leadership characterized by the following dimensions: (ideal influence, inspirational motivation, intellectual stimulation, considerations Individualism, empowerment), and the answers of the respondents agreed on a high degree of agreement on the existence of these dimensions, so that there is an effect of the independent variable, transformational leadership in its various dimensions (ideal influence, inspirational motivation, intellectual stimulation, individual considerations, empowerment) on the dependent variable (marketing creativity). The study presented several recommendations, the most important of which were paying attention to spreading the culture of transformational leadership among employees in Jordanian commercial banks in the northern region, providing opportunities and empowering distinguished employees to take positions appropriate to their potential that would benefit their banks.